The Influence of Learning Model and Learning Independence on 11th Students' Learning Outcomes in Entrepreneurship Subject SMK N 7 Medan - Ummi Chairani; Dede Ruslan; Arwansyah (Britain International for Academic Research (BIAR) Publisher, 2020)
The purpose of this study were to (1) find out and analyze between the Advance Organizer learning model and the Discovery Learning learning model towards learning outcomes in entrepreneurship subjects in class XI SMK N 7 Medan, (2) Knowing and analyzing learning independence using the Advance Organizer learning model with learning independence that uses the Discovery Learning model of learning outcomes on entrepreneurship subjects in 11th Grade Students in SMK N 7 Medan. This research was conducted at SMK N 7 Medan which is located at JL. STM. No. 12 E Medan. The subjects of this study were 71 11th grade Ak students. Data collection techniques and instruments use tests and questionnaires. The results showed (1) the difference in student entrepreneurship learning outcomes taught by using the Advamce Organizer learning model with the learning outcomes of students who were taught using the Discovery Learning learning model with a Fcount score of 4.59 and a Ftable of 3.94. (2) Differences in student entrepreneurship learning outcomes that have high learning independence and entrepreneurial learning outcomes of students who have low learning independence with a Fcount score of 6.04 and Ftable of 3.94. So it can be concluded that the results of student entrepreneurship learning are taught by using the Advance Organizer learning model and have higher learning independence than using the Discovery Learning model.